Cancer risks in Crohn disease patients - Hemminki, K.; Li, X.; Sundquist, J.; Sundquist, K. (Annals of oncology, 2009)
Background: Patients diagnosed with Crohn disease (CD) are known to be at an increased risk of bowel cancers and lymphoma. CD is an autoimmune disease and we hypothesize that the patients are predisposed to a wider spectrum of cancers. Patients and methods: A CD research database was constructed by identifying hospitalized CD patients from the Hospital Discharge Register and cancer patients from the Swedish Cancer Registry. Follow-up of 21 788 CD patients first hospitalized during the years 1964–2004 identified 1424 cancer cases. Standardized incidence ratios (SIRs) were calculated by comparing cancers in CD patients with subjects without CD. Results: In addition to the known sites, many additional sites were in excess in CD patients. These included liver, pancreatic, lung, prostate, testicular, kidney and skin (squamous cell) cancers; nonthyroid endocrine tumors and leukemia. The previously established sites showed the highest SIRs; however, SIRs >2.0 were noted for the novel sites of the liver, testis and kidney. For testicular cancer, the SIR of seminoma was 2.74. Cancer risks were influences by age at first hospitalization for CD but whether the age effects were increasing or decreasing depending on the cancer type. Conclusions: This large study identified many novel subsequent cancers in CD patients.